18-month hydration of a low-pH cement for geological disposal of radioactive waste: The Cebama reference cement. (May 2020) - Vasconcelos, Rita G.W.; Walkley, Brant; Day, Sarah; Tang, Chiu C.; Paraskevoulakos, Haris; Gardner, Laura J.; Corkhill, Claire L.
Abstract: Low-pH cements are candidate materials for use in the construction of geological disposal facilities for the long-term management of nuclear waste. Since these facilities will operate over long time scales, the changes in mineralogy and microstructure require evaluation as a function of time. As a first step towards this understanding, the hydration of a standardised low-pH cement paste, known as the Cebama reference cement, was investigated over an 18-month period. Characterisation was performed at 28 days of curing, at 20 °C and 40 °C, and novel synchrotron radiation X-ray diffraction experiments were performed, in-situ, from 90 min to 18 months of curing. Concurrent solid state 29 Si and 27 Al MAS NMR data were acquired for parallel samples to quantify the extent of cement hydration and the composition and mean chain length of the predominant calcium aluminosilicate hydrate (C-(A)-S-H) reaction product. After 18 months, cement clinker phases were still present, highlighting the slow hydration kinetics of this low-pH cement. The data presented provide a benchmark for ongoing and future studies of low-pH cements in geological disposal environments, over extended time scales. Highlights: Investigation of a low pH cement paste for radioactive waste disposal. Kinetics and composition of cement hydrate minerals investigated over 18 months. Synchrotron X-ray diffraction revealed the composition of cement hydrates. Solid state NMR used to quantify C-A-S-H formation kinetics and structure. Data support EU geological disposal of radioactive waste benchmark experiments.